2017
DOI: 10.1021/acs.jpcc.7b06043
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Dynamics That Control the Activity of Ceria–Zirconia Solid Solutions in Thermochemical Water Splitting Cycles

Abstract: The reactivity of a ceria-rich Ce0.85Zr0.15O2 solid solution towards the thermochemical water splitting process (TWS) was studied over repeated H2/H2O redox cycles. The structural and surface modifications after treatment at high temperature under air or N2 atmospheres were characterized by High-Resolution Transmission Electron Microscopy (HRTEM), X-ray diffraction (XRD), Raman spectroscopy, X-ray Photoemission Spectroscopy (XPS) and Positron Annihilation Lifetime Spectroscopy (PALS). Samples treated under nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 62 publications
2
20
1
Order By: Relevance
“…Five "u" and five "v" peaks were identified, related to 3d 5/2 and 3d 3/2 states, respectively. The v • , v', u • and u' peaks were ascribed to Ce 3+ ions, while the other six peaks were assigned to the 4+ oxidation state [33,34]. A similar deconvolution was performed on the Pr 3d XP spectrum, in the 968-923 eV region (Figure 5b), ascribing four peaks (herein denoted as a • , a', b • and b') to Pr 3+ ions and other six peaks to the 4+ oxidation state [35].…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…Five "u" and five "v" peaks were identified, related to 3d 5/2 and 3d 3/2 states, respectively. The v • , v', u • and u' peaks were ascribed to Ce 3+ ions, while the other six peaks were assigned to the 4+ oxidation state [33,34]. A similar deconvolution was performed on the Pr 3d XP spectrum, in the 968-923 eV region (Figure 5b), ascribing four peaks (herein denoted as a • , a', b • and b') to Pr 3+ ions and other six peaks to the 4+ oxidation state [35].…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…Previous research has reported on H 2 /H 2 O cycling, outlining that it can be used to define the splitting properties of materials (Landi, 2019). Results of thermogravimetric (TG) measurements (reduction under inert Ar atmosphere; oxidation under 40 vol.% CO 2 /Ar) and H 2 O splitting tests on H 2 -reduced samples were successfully compared (Al-Shankiti et al, 2013;Pappacena et al, 2016Pappacena et al, , 2017Luciani et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…As previously reported (Luciani et al, 2018(Luciani et al, , 2019Portarapillo et al, 2019), the samples were pre-treated in a hydrogen flow (TPR; 10 l(SLT)/h; 5 vol.% H 2 /N 2 ) up to approximately 1,000 • C, heating rate 10 • C/min (Al-Shankiti et al, 2013;Pappacena et al, 2016Pappacena et al, , 2017 and cooled down to 60 • C under a nitrogen flow. TPO was then carried out by flowing (i) a 3 vol.% H 2 O/N 2 mixture (10 l(SLT)/h), (ii) a 6 vol.% CO 2 /N 2 mixture (10 l(SLT)/h), (iii) a (6 vol.% H 2 O + 6 vol.% CO 2 )/N 2 mixture (10 l(SLT)/h); the temperature raised up to about 1,000 • C (heating rate: 10 • C/min; time at the maximum temperature: 20 min).…”
Section: H 2 O/co 2 Splitting and Co-splitting Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…During recent decades, research on photocatalytic water-splitting and CO 2 reduction started to draw more attention. It should be noted that there are numerous publications reporting 'achievement' of H 2 production via water splitting using various kinds of sacrificial reagents, such as methanol, amine and amide among others [25,[32][33][34][35][36][37][38][39][40][41][42]. However, it is worth noting that H 2 production reactions are not likely to be considered as a genuine 'water-splitting' reaction.…”
Section: Introductionmentioning
confidence: 99%